THE AUTOBIOGRAPHICAL NATURE OF THE ALLEGORY IN WOLE SOYINKA’S DEATH AND THE KING’S HORSEMAN - Moffat Moyo (European Scientific Journal, ESJ, 2014)
This work examines Wole Soyinka’s use of the allegory through which he sneaks himself into the text of Death and the King’s Horseman. Using the theory of New Historicism which claims that there is a relationship between the text and the historical milieu of the text, the paper explores Soyinka’s background and relates it to the text under discussion. Particular emphasis is placed on the parallel between Soyinka and the character Olunde in the play. It is concluded that through Olunde, Soyinka creeps into the text. This is due to the understanding that Olunde represents the African who has been to England to learn not only the English culture but also healing for his land hence returns to the healing of his land. The parallel is shown through Soyinka’s studying of theatre and Olunde’s studying of medicine in England.